Adapting the Diabetes Prevention Program for low and middle-income countries: protocol for a cluster randomised trial to evaluate ‘Lifestyle Africa’ - Thandi Puoane; Ken Resnicow; Naomi Levitt; Estelle V Lambert; Joshua M Smyth; Delwyn Catley; Lungiswa Tsolekile; Kandace Fleming; Emily A Hurley; Mara Z Vitolins; Kathy Goggin (BMJ Open)
Introduction Low and middle-income countries like South Africa are experiencing major increases in burden of non-communicable diseases such as diabetes and cardiovascular conditions. However, evidence-based interventions to address behavioural factors related to these diseases are lacking. Our study aims to adapt the CDC’s National Diabetes Prevention Program (DPP) within the context of an under-resourced urban community in Cape Town, South Africa.Methods/analysis The new intervention (Lifestyle Africa) consists of 17 weekly sessions delivered by trained community health workers (CHWs). In addition to educational and cultural adaptations of DPP content, the programme adds novel components of text messaging and CHW training in Motivational Interviewing. We will recruit overweight and obese participants (body mass index ≥25 kg/m2) who are members of 28 existing community health clubs served by CHWs. In a 2-year cluster randomised control trial, clubs will be randomly allocated to receive the intervention or usual care. After year 1, usual care participants will also receive the intervention and both groups will be followed for another year. The primary outcome analysis will compare percentage of baseline weight loss at year 1. Secondary outcomes will include diabetes and cardiovascular risk indicators (blood pressure, haemoglobin A1C, lipids), changes in self-reported medication use, diet (fat and fruit and vegetable intake), physical activity and health-related quality of life. We will also assess potential psychosocial mediators/moderators as well as cost-effectiveness of the programme.Ethics/dissemination Ethical approval was obtained from the University of Cape Town and Children’s Mercy. Results will be submitted for publication in peer-reviewed journals and training curricula will be disseminated to local stakeholders.Trial registration number NCT03342274.